Pengaruh Digital Marketing, Inovasi Produk, dan Orientasi Kewirausahaan Terhadap Kinerja Pemasaran UMKM (Studi Kasus UMKM Binaan Rumah BUMN Cilacap) - Elina Febriyanti; Hakim Hakim; Ainur Latif (Jurnal Ilmiah Ekonomi dan Manajemen Indonesia, 2026)
This study aims to analyze the influencedigital marketing, product innovation, and entrepreneurial orientation on the marketing performance of MSMEs fostered by Rumah BUMN Cilacap, both partially and simultaneously. The background of this research is based on the marketing performance of MSMEs fostered by Rumah BUMN Cilacap, which is not yet fully optimal despite having received various related training.digital marketing, product innovation, and entrepreneurship. This study uses a quantitative approach with an associative method. The population in this study were all MSMEs fostered by Rumah BUMN Cilacap. Sampling was determined using the Slovin formula with a total of 81 respondents. The data analysis method used was multiple linear regression. The results of the study indicate thatdigital marketinghas a positive effect on marketing performance, product innovation has a positive effect and is the most dominant variable influencing marketing performance, while entrepreneurial orientation does not have a significant effect on marketing performance. Simultaneously,digital marketing, product innovation, and entrepreneurial orientation influence marketing performance. The coefficient of determination (R²) value is 0.628, indicating that the independent variables are able to explain 62.8% of the variation in marketing performance. The results of this study indicate the importance of developing sustainable product innovation and optimizing marketing performance.digital marketingto improve the marketing performance of MSMEs and the need for the implementation of a more applicable entrepreneurial orientation in marketing strategies.